2021
DOI: 10.1016/j.ejpn.2021.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of brain abnormalities for cognitive functioning in cerebral palsy: A prospective cohort study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
9
1
Order By: Relevance
“…Our results support these previous findings by limiting analyses to participants with the same CP motor type and using a more detailed measure of IQ. In contrast, Moll et al found that the extent of white matter damage and GMFCS level are prognostic factors for presenting with a non-verbal IQ ≤ 70 (Moll et al, 2021). The inconsistency between our findings and those of Moll et al´s study (which also used a semiquantitative approach) may be due IQ being treated as continuous variable in our study, rather than applying an IQ cut-off.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results support these previous findings by limiting analyses to participants with the same CP motor type and using a more detailed measure of IQ. In contrast, Moll et al found that the extent of white matter damage and GMFCS level are prognostic factors for presenting with a non-verbal IQ ≤ 70 (Moll et al, 2021). The inconsistency between our findings and those of Moll et al´s study (which also used a semiquantitative approach) may be due IQ being treated as continuous variable in our study, rather than applying an IQ cut-off.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies that have explored the association between general intellectual functioning and brain structure in children with spastic motor type CP mostly used categorical descriptions of lesion patterns (Ahlin et al, 2017;Cioni et al, 1999;Himmelmann et al, 2021;Himmelmann and Uvebrant, 2011;Reid et al, 2018;Stadskleiv et al, 2018) and did not use standarized IQ measures. In children with spastic motor type CP, only three studies have investigated the relationship between general intellectual functioning and MRI characteristics other than the lesion pattern (Moll et al, 2021;Rai et al, 2013;S. M. Reid et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Raven's Coloured Progressive Matrices (RCPM) test is a shorter, simpler form of Raven's progressive matrices test that can be used in persons with severe motor impairment and speech limitations. The RCPM has been widely used as a global cognitive measure to assess mental age or non-verbal intelligence in children with CP (Kiessling et al 1983;Falkman et al 2002;Asbell et al 2010;Asano & Morioka 2017;Laporta-Hoyos et al 2017;Moll et al 2021). RCPM aims to measure fluid intelligence by perceiving the relationships and belongingness between abstract patterns (Spearman 1961).…”
Section: Introductionmentioning
confidence: 99%
“…2017; Moll et al . 2021). RCPM aims to measure fluid intelligence by perceiving the relationships and belongingness between abstract patterns (Spearman 1961).…”
Section: Introductionmentioning
confidence: 99%
“…Sixty to 70% of individuals with CP can walk; however, many need support, such as ankle foot orthoses (AFOs). 5,6 AFOs are often prescribed to support the weak ankle dorsiflexors and stretch the spastic plantarflexors (preventing shortening and deformities), with the aim to improve the gait pattern. 7 Many types of AFO are available; generally, they improve stride length, walking speed, and ankle dorsiflexion at the initial contact and during the swing phase.…”
mentioning
confidence: 99%